Bioactive Compounds in Milk Fat and Their Impact on Human Health - Mila Arapceska; Zivko Jankuloski; Hajrulai Musliu, Zehra; Nikolche Jankulovski; Uzunov, Risto (My University, 2015)
Milk and dairy products have long traditions in human nutrition. Milk composition is rather than complex. Its constituents have been for many years on the priority list of research, with their positive and negative effects on human health. The most variable component of milk is milk fat. It is one of the components which determine nutritive quality and technological performance of milk. Milk fat contains a number of components which are metabolically active such as: sphingolipids, conjugated linoleic acids (CLA), butyric acid, other fatty acids, vitamins A and D. A variety of health benefits have been associated with these compounds.The study of bioactive compounds in milk fat is very important for understanding their physiological and biochemical functions which have crucial impacts on human metabolism and health.
Keywords: milk fat, conjugated linoleic acids (CLA), health benefits